PERAN ROH KUDUS DALAM KEHIDUPAN ORANG PERCAYA MENURUT KITAB PERJANJIAN BARU - Nasya Teopila; Markelina Markelina; Luri Trikristiani; Sarmauli Sarmauli (Adisam Publisher, 2025)
This study highlights the urgent need to comprehensively understand the function of the Holy Spirit, which is triggered by theological confusion that still prevails among believers. The main objective of this study is to comprehensively examine and compile various aspects of the role of the Holy Spirit as described in the New Testament, in order to provide an integrated and applicable framework in Christian life. Using a qualitative approach through a literature review (pneumatology), this study primarily examines the New Testament as the primary source, accompanied by secondary references such as theology books and journals. The findings of this study reinforce the main thesis, concluding that the Holy Spirit is a Divine Person whose activities changed from being selective and temporary in the Old Testament to being universal and eternal in the New Testament. Further research shows that the Holy Spirit's functions can be organized into two essential roles, namely as the Sanctifier (internal character formation) and the Paraclete (Helper, Comforter, and External Empowerer). Overall, this study emphasizes that an integrated understanding of the Holy Spirit's role provides a solid theological foundation and practical model for spiritual development, encouraging a more conscious dependence on the Holy Spirit in achieving holiness and mission service.